The role of Human Resources transformation in the strategy enactment in the electricity company of Eswatini - Mtetwa, Trevor Ncamiso; Khumalo, Njabulo (Technium Social Sciences Journal, 2022)
Over the years the function of HR has transformed in an attempt to respond and align to changes and demands of the business environment. The purpose of this article was to explore the role of HR transformation in strategy enactment in the Electricity Company of Eswatini. To help HR personnel in Eswatini to gain and understanding in strategy enactment planning and strategic business operations since the changes in HR not only have implications for business operations, but also implicate the businesses that are positioned to respond to the changes. Questionnaires were personally distributed by the researcher to a sample of 28 management staff in the company. Descriptive statistics were used in analysing data. The strategy enactment requires HR to be active, prioritize value-adding actions and take lead in introducing the strategic HRM. This study highlights the linking between successful talent management and HR transformation. Managers and HR professionals as the role players and drivers of the process, it imperative that they possess more in-depth competencies and knowledge on the nitty-gritties of the implementation of TM. This study contributes to the body of knowledge concerning the dynamic nature of human capital necessities and the business environments frequent knowledge generation in order to assist businesses in positioning themselves in addressing talent management needs.